(untitled) (Papeles, 2024)
This article discusses the process and results of an innovative online international learning experience aimed at internationalizing the curriculum both James Madison University (JMU) and Universidad Nacional del Litoral (UNL). The initiative is part of a broader strategy to promote global competence among studentes by integrating international perspectives into their academic programs without requiring physical travel.